The Effect of Workload and Role Conflict on Work-Life Balance: The Mediating Role of Work Stress - Dewayani, Amanda Zahra; Dihan, Fereshti Nurdiana (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of workload and role conflict on work-life balance, with work stress as an intermediary variable. The background of this study is based on the importance of maintaining a balance between an employee's work and personal life, which is influenced by various factors such as workload, role conflict, and work stress. The method used is a quantitative approach with a questionnaire as the instrument, while data analysis is performed using multiple linear regression and path analysis using SPSS software. The results of the study show that: 1) workload has a negative but insignificant effect on work-life balance; 2) role conflict has a negative and significant effect on work-life balance; 3) workload has a positive and significant effect on work stress; 4) role conflict has a positive but insignificant effect on work stress; 5) work stress has a negative and significant effect on work-life balance; 6) work stress is able to mediate the effect of workload on work-life balance; and 7) work stress is not able to mediate the effect of role conflict on work-life balance. Practically, this study provides recommendations for companies to improve work systems related to workload distribution, reduce employee stress levels, clarify tasks and responsibilities, and implement employee welfare programs.